Neonatal hypoglycemia in dogs—pathophysiology, risk factors, diagnosis and treatment - Fuchs, Kárita da Mata [UNESP]; Pereira, Keylla Helena Nobre Pacífico [UNESP]; Xavier, Gleice Mendes [UNESP]; Mendonça, Júlia Cosenza [UNESP]; Barreto, Renata Oliveira [UNESP]; Silva, Renata Cesar [UNESP]; de Souza, Fabiana Ferreira [UNESP]; Lourenço, Maria Lucia Gomes [UNESP] (Frontiers, 2024)
Hypoglycemia is the most common metabolic alteration in the clinical routine of newborn dogs, acting as a predictor of mortality in these patients. The neonatal dog shows hepatic insufficiency and homeostatic mechanisms not yet fully developed, with limited glycogen reserves and limited capacity to perform glycogenolysis and gluconeogenesis. These physiological particularities make newborn dogs particularly susceptible to hypoglycemia when of fasting, even for short periods. Several maternal and neonatal factors may be related to a higher risk of developing hypoglycemia in neonates. This paper reviews glycemic homeostasis, the pathophysiology of neonatal hypoglycemia, the main causes involved and the diagnostic and therapeutic approaches to this condition.
Keywords: dog; glycemia; glycemic homeostasis; metabolism; puppy